2021
DOI: 10.14710/jil.19.2.365-371
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Temple Waste into Organic Incense as Temple Environment Preservation in Bali Island

Abstract: Kegiatan upacara di tempat suci pura di Pulau Bali rata-rata menghasilkan sampah sekitar 2000 L/hari. Sebagai bagian yang sangat penting dari budaya Bali, sesajen yang terdiri dari bunga, daun, buah-buahan dan bambu disajikan di setiap upacara keagamaan. Pembuangan sampah pura yang tidak tepat berpotensi menimbulkan gangguan pada kehidupan manusia dan lingkungan, seperti air dan sanitasi, penumpukan sampah, peningkatan tingkat pencemaran, dan kesehatan manusia. Penelitian ini bertujuan untuk mendaur ulang samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Figure 6 illustrates the effect of dyebath pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) on K/S values of the dyed fabrics. It is observed that the optimum K/S is obtained at acidic pH of 4.…”
Section: Effect Of Ph In Dyeing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 illustrates the effect of dyebath pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) on K/S values of the dyed fabrics. It is observed that the optimum K/S is obtained at acidic pH of 4.…”
Section: Effect Of Ph In Dyeing Processmentioning
confidence: 99%
“…The improper disposal of such waste creates an array of environmental and human health problems [2,3]. According to the WHO, 36% of the chemicals used in flower farms are extremely toxic, and when discarded in landfills, they can produce 22 times more environmentally destructive greenhouse gases than carbon dioxide [4]. The appropriate management of such waste could provide as converting them into useful or value-added products such as biochar, biofertilizer, dye extraction, essential oil, color powder, biogas, etc.…”
Section: Introductionmentioning
confidence: 99%
“…During the ceremonial day, the temple waste significantly increases due to incoming visitors. The waste container could be overloaded; some waste is dumped out and damages the environment [4]. Improper waste management has damaged the ecosystem aligning with the impact on the living creatures [5].…”
Section: Introductionmentioning
confidence: 99%
“…Temple waste was dominated by offerings waste, flowers, leaves, and other waste in the form of leftover food, fruit, bamboo, cloth, and plastic. The types of temple waste components were influenced by visitors, because each visitor brings different offerings, according to their socio-economic conditions [15]. As with waste generation, the composition of waste is also influenced by several factors: 1.…”
Section: Introductionmentioning
confidence: 99%
“…Belum adanya lahan yang dapat dimanfaatkan dalam hal ini menjadi tantangan bagi masyarakat desa untuk dapat mengolah sampahnya secara mandiri. Sampah yang dikumpulkan di Desa Ayunan sejauh ini masih langsung dibawa ke TPA Regional Sarbagita (Soedjono et al, 2017;Wijaya et al, 2021) permasalahan yang dialami oleh mitra sesuai dengan prioritasnya, adalah sebagai berikut:1) Belum tersedianya lahan untuk tempat pengolahan sampah di Desa Ayunan yang berdampak pada minimnya upaya pengelolaan sampah. Sistem pengelolaan sampah seharusnya terus berjalan tanpa bergantung pada ketersediaan lahan untuk tempat pengolahan sampah komunal.…”
unclassified